Systemic Treatment of Psoriasis with JAK Inhibitors: A Review - Kvist-Hansen, Amanda (Dermatol Ther (Heidelb), 2019)
Psoriasis is a prevalent chronic inflammatory disease. The inflammatory response is driven by T cells and mediated by multiple cytokines such as tumor necrosis factor and the interleukins IL-17 and IL-23. Moderate-to-severe psoriasis is treated systemically, using either biologics or conventional treatments with small-molecule drugs. The newer biologics are very effective and well tolerated, but not all patients respond to treatment with biologics, so there is a need for new treatment options for psoriasis. Janus kinase (JAK) inhibitors are a new drug class that may be of use in this respect. These inhibitors are already on the market for rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis. They block the intracellular signal pathway mediated by JAK and signal transducer and activator of transcription (STAT) proteins, thereby inhibiting gene transcription of proinflammatory cytokines. JAK inhibitors are currently being tested as potential treatments for psoriasis. They have shown clinical efficacy as measured by the Psoriasis Area and Severity Index 75 response in both phase 2 and 3 trials, and appear to be well tolerated overall. This review provides an overview of the mechanisms underlying the actions of JAK inhibitors in psoriasis, together with the results of clinical trials testing their efficacies when used to treat the disease.